Cobre sérico e enzimas relacionadas ao seu metabolismo em ovinos preparados para exposição e criados a campo na depressão central do estado do Rio Grande do Sul - Rezler, Ubiratã (2007)
The objective of the present work was to identify serum copper levels and aspartateaminotransferase (AST) and gamagluthamyl transferase (GGT) activity in purebred show and field raised sheep and to contribute to formation of regional reference values. Blood samples of 120 show sheep and 110 field raised animals were collected independently of age, sex and breed. Means serum levels of copper for show and field sheep 66.14 ± 9.76 and 62.01 ±16.36 μg.dl-1 (P<0.0357), respectively; AST activity was higher in show sheep than in field animals (85.01 ±40.02 vs. 65.58 ±16.19 IU, P<0.0001); GGT activity was 41.02 ±10.61 and 41.91 ±9.49 IU with no differences between groups. In conclusion, serum copper levels in all show animals were within international reference values, whereas field raised animals presented several individuals that fell bellow the lower limit. Serum activitiy of AST and GGT appear not to be related to copper metabolism in these animals.